A study of outcome of neuroparalytic snake bite patients treated with fixed dose of antisnake venom - Kakaria, Ashish S.; Narkhede, Meenakshi; Agrawal, Sanjay; Bhavsar, Abhijit; Nukte, Vivek (International Journal of Research in Medical Sciences, 2017)
Background: Dhule district in Maharashtra (India) has snake bite as a common medical emergency. There are 168 villages in Dhule district and its majority of the population is engaged in farming and snakebite is a major occupational hazard particularly during the harvesting season. The available data on the epidemiology of snake bite from the here is sparse. Poisonous and nonpoisonous snake bites accounts approximately 30 admissions per month which increase to 35-40 admissions in rainy season in Civil Hospital. Methods: Fifty patients with severe neuroparalytic snake envenomation, resulting in acute type II respiratory failure, admitted to medical ICU for mechanical ventilation during one year period, were studied. Ventilatory requirements, amount of antisnake venom (ASV) infused, period of neurological recovery and hospital survival were evaluated. Results: 60% of patients affected were in the age group of 21-40 years. Maximum numbers of bites were during April to September (84%). All patients had severe manifestations such as ptosis, ophthalmoplegia, neck muscle weakness, limb and respiratory muscle weakness. 200 ml ASV was administered to all, along with atropine and neostigmine. Mechanical ventilation was required for a median duration of 26.60 hours. All victims in the study group survived with complete neurological recovery except one mortality for a patient who had suffered irreversible hypoxic cerebral injury prior to arrival in hospital and needed ventilatory support for 9.58 days. Conclusions: Timely institution of ventilatory support and fixed dose of 200 ml of ASV along with anticholinesterase treatment was sufficient to reverse neuroparalysis in severe elapid bites.